The Universal Presence of the Reynolds Number - Aldo Tamburrino; Yarko Niño (Fluids)
The Reynolds number is a fundamental parameter in fluid dynamics, initially introduced by O. Reynolds in 1883 to characterize the transition between laminar and turbulent flow in fluids and necessary in the scaling of viscous resistance. Over time, its application has expanded significantly, becoming essential for studying a vast range of fluid phenomena—from microscopic scales such as cellular motion to macroscopic scales like turbulent flows and even intergalactic dynamics. The article highlights the universal relevance of the Reynolds number across various fields, including its adaptation to non-Newtonian fluids and granular flows. It emphasizes how the Reynolds number has evolved from a simple dimensionless group to a critical tool for understanding complex physical processes across different scales and environments.